A new nanoporous alucone-amine hybrid membrane with extremely high CO2/CH4 selectivity - Aynaz Meshkat; Abbas Ali Khodadadi; Yadollah Mortazavi; Muhammad Sahimi (Environmental Research, 2026)

Whither hydrology? Looking back to move ahead - Allen G. Hunt; Muhammad Sahimi; Behzad Ghanbarian (Hydrological Sciences Journal, 2026)

Geologic hydrogen as an emerging fuel: experimental insights, thermodynamics, kinetics, and reactive transport modeling - Rasoul Moradi; M. Sadegh Rajabi; Hamid Didari; Birendra Jha; Muhammad Sahimi (Fuel, 2026)

Inferring shallow storage properties from the analysis of percolation theory of streamflow elasticity - Allen G. Hunt; Behzad Ghanbarian; Muhammad Sahimi (Science of The Total Environment, 2025)

Resilience underground: Understanding earthworm biomass responses to land use changes in the tropics - Badrul Azhar; Peter van der Meer; Rutger F. Sterenborg; Muhammad Syafiq Yahya; Norhisham Razi; Maisarah Burhanuddin; Jasmijn Rookmaker; Nur Syarihah Sahimi; Welmoed van der Pal; Frisco Nobilly; Siti Aisyah Mohd Azam; Meriam Ubachs; et al. (Biological Conservation, 2024)

The Transition from Darcy to Nonlinear Flow in Heterogeneous Porous Media: I—Single-Phase Flow - Sepehr Arbabi; Muhammad Sahimi (Transport in Porous Media, 2024)
Using extensive numerical simulation of the Navier–Stokes equations, we study the transition from the Darcy’s law for slow flow of fluids through a disordered porous medium to the nonlinear flow regime in which the effect of inertia cannot be neglected. The porous medium is represented by two-dimensional slices of a three-dimensional image of a sandstone. We study the problem over wide ranges of porosity and the Reynolds number, as well as two types of boundary conditions, and compute essential features of fluid flow, namely, the strength of the vorticity, the effective permeability of the pore space, the frictional drag, and the relationship between the macroscopic pressure gradient $${\varvec{\nabla }}P$$ ∇ P and the fluid velocity v . The results indicate that when the Reynolds number Re is low enough that the Darcy’s law holds, the magnitude $$ω _z$$ ω z of the vorticity is nearly zero. As Re increases, however, so also does $$ω _z$$ ω z , and its rise from nearly zero begins at the same Re at which the Darcy’s law breaks down. We also show that a nonlinear relation between the macroscopic pressure gradient and the fluid velocity v , given by, $$-{\varvec{\nabla }}P=(μ /K_e)v+β _nρ |v|^2v$$ - ∇ P = ( μ / K e ) v + β n ρ | v | 2 v , provides accurate representation of the numerical data, where $$μ$$ μ and $$ρ$$ ρ are the fluid’s viscosity and density, $$K_e$$ K e is the effective Darcy permeability in the linear regime, and $$β _n$$ β n is a generalized nonlinear resistance. Theoretical justification for the relation is presented, and its predictions are also compared with those of the Forchheimer’s equation.

Interpreting water demands of forests and grasslands within a new Budyko formulation of evapotranspiration using percolation theory - Allen G. Hunt; Muhammad Sahimi; Boris A. Faybishenko; Markus Egli; Behzad Ghanbarian; Fang Yu (Science of The Total Environment, 2023)

The Potential of Quantum Computing for Geoscience - Muhammad Sahimi; Pejman Tahmasebi (Transport in Porous Media, 2022)

Universal Frequency-Dependent Permeability of Heterogeneous Porous Media: Effective–Medium Approximation and Critical-Path Analysis - Muhammad Sahimi (Transport in Porous Media, 2022)

Flow and Transport Properties of Deforming Porous Media. II. Electrical Conductivity - Samuel Richesson; Muhammad Sahimi (Transport in Porous Media, 2021)

Flow and Transport Properties of Deforming Porous Media. I. Permeability - Samuel Richesson; Muhammad Sahimi (Transport in Porous Media, 2021)

Speeding-up Simulation of Multiphase Flow in Digital Images of Heterogeneous Porous Media by Curvelet Transformation - Abdullah Aljasmi; Muhammad Sahimi (Transport in Porous Media, 2021)

Identifying the Optimal Path and Computing the Threshold Pressure for Flow of Bingham Fluids Through Heterogeneous Porous Media - Hamid Didari; Hassan Aghdasinia; Mahdi Salami Hosseini; Fatemeh Ebrahimi; Muhammad Sahimi (Transport in Porous Media, 2020)

A Study of the Role of Microfractures in Counter-Current Spontaneous Imbibition by Lattice Boltzmann Simulation - Yang Liu; Jianchao Cai; Muhammad Sahimi; Chaozhong Qin (Transport in Porous Media, 2020)

Linking Morphology of Porous Media to Their Macroscopic Permeability by Deep Learning - Serveh Kamrava; Pejman Tahmasebi; Muhammad Sahimi (Transport in Porous Media, 2020)

Upscaling of Geological Models of Oil Reservoirs with Unstructured Grids Using Lifting-Based Graph Wavelet Transforms - Amin Rezapour; Antonio Ortega; Muhammad Sahimi (Transport in Porous Media, 2019)

Editorial to the Special Issue on Reconstruction of Porous Media and Materials and Its Applications - Pejman Tahmasebi; Muhammad Sahimi (Transport in Porous Media, 2018)

Thermal Conduction in Deforming Isotropic and Anisotropic Granular Porous Media with Rough Grain Surface - Roohollah Askari; S. Hossein Hejazi; Muhammad Sahimi (Transport in Porous Media, 2018)

Rapid Learning-Based and Geologically Consistent History Matching - Pejman Tahmasebi; Muhammad Sahimi; Mehrdad G. Shirangi (Transport in Porous Media, 2018)

Electrical Conductivity of Partially Saturated Packings of Particles - Behzad Ghanbarian; Muhammad Sahimi (Transport in Porous Media, 2017)

Molecular Dynamics Simulation of Transport and Separation of Carbon Dioxide–Alkane Mixtures in a Nanoporous Membrane Under Sub- and Supercritical Conditions - Mahnaz Firouzi; Muhammad Sahimi (Transport in Porous Media, 2016)

Pore-Network Simulation of Unstable Miscible Displacements in Porous Media - Mahnaz Hekmatzadeh; Mitra Dadvar; Muhammad Sahimi (Transport in Porous Media, 2016)

Three-Dimensional Stochastic Characterization of Shale SEM Images - Pejman Tahmasebi; Farzam Javadpour; Muhammad Sahimi (Transport in Porous Media, 2015)

Geostatistical Simulation and Reconstruction of Porous Media by a Cross-Correlation Function and Integration of Hard and Soft Data - Pejman Tahmasebi; Muhammad Sahimi (Transport in Porous Media, 2015)

Multiple-point geostatistical modeling based on the cross-correlation functions - Pejman Tahmasebi; Ardeshir Hezarkhani; Muhammad Sahimi (Computational Geosciences, 2012)

Analysis of Cross Correlations Between Well Logs of Hydrocarbon Reservoirs - Hassan Dashtian; G. Reza Jafari; Zahra Koohi Lai; Mohsen Masihi; Muhammad Sahimi (Transport in Porous Media, 2011)

Upscaled Unstructured Computational Grids for Efficient Simulation of Flow in Fractured Porous Media - Muhammad Sahimi; R. Darvishi; Manouchehr Haghighi; M. Reza Rasaei (Transport in Porous Media, 2010)

Book review: Percolation Theory for Flow in Porous Media, by A Hunt (Springer, Berlin, 2005) - Muhammad Sahimi (Hydrogeology Journal, 2009)

Upscaling of the permeability by multiscale wavelet transformations and simulation of multiphase flows in heterogeneous porous media - M. Reza Rasaei; Muhammad Sahimi (Computational Geosciences, 2009)

Upscaling and Simulation of Waterflooding in Heterogeneous Reservoirs Using Wavelet Transformations: Application to the SPE-10 Model - Mohammad Reza Rasaei; Muhammad Sahimi (Transport in Porous Media, 2008)

Multiresolution Wavelet Scale Up of Unstable Miscible Displacements in Flow Through Heterogeneous Porous Media - Fatemeh Ebrahimi; Muhammad Sahimi (Transport in Porous Media, 2004)

Invasion Percolation on Correlated and Elongated Lattices: Implications for the Interpretation of Residual Saturations in Rock Cores - Mark A. Knackstedt; S. J. Marrink; Adrian P. Sheppard; W. V. Pinczewski; Muhammad Sahimi (Transport in Porous Media, 2001)

The Effect of Asphalt Precipitation on Flow Behavior and Production of a Fractured Carbonate Oil Reservoir During Gas Injection - Muhammad Sahimi; Ali Reza Mehrabi; Nabiollah Mirzaee; Hossein Rassamdana (Transport in Porous Media, 2000)